Issues in the Reform of Deposit Insurance and Regulation of Depository Institutions. (IMF Working Papers; Working Paper ;, 1990)
In the United States, the thrift industry crisis and evidence of financial weakness in the banking industry have raised concerns about the cost-effectiveness of the present framework of deposit insurance and regulation of depository institutions that serves to control systemic risks. The reform proposals discussed in this paper aim to create a more cost-effective approach by either modifying the operation of the deposit insurance funds to reduce the value of the deposit guarantee or altering those regulations of depository institutions that limit portfolio risk to reduce their overall cost. Consideration is given to both the potential effectiveness and practicability of the proposed reforms.